2020
DOI: 10.1177/1010539520931328
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Complementary Feeding of Infants in the Asia Pacific Region: APACPH Public Health Nutrition Group

Abstract: Good nutrition in the first “1000 days,” including breastfeeding and appropriate complementary foods, prepares for a healthy childhood and adult life, also contributes to the prevention of the double burden of malnutrition. Exclusive breastfeeding provides all required nutrients until an infant is around 6 months of age when complementary foods are needed. A literature review was undertaken of complementary foods in the Asia Pacific region. The foods being used at present are often of low nutrient density may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 55 publications
0
22
0
4
Order By: Relevance
“…Appropriate CF is characterized by fulfilment of its general principles, including starting the CF at 6 months with continuing breastfeeding; meet the minimum dietary frequency, amount, and variation; gradually increasing texture; practicing responsive feeding, good hygiene, and proper food handling. 3 Furthermore, based on this study result, we find that mother CF knowledge (P = .002), child's age (P = .019), and household food security(P = .006) were the factors associated with appropriate CF practices in the context of COVID-19 outbreaks.…”
Section: Factors Related To Cf Practicesmentioning
confidence: 65%
“…Appropriate CF is characterized by fulfilment of its general principles, including starting the CF at 6 months with continuing breastfeeding; meet the minimum dietary frequency, amount, and variation; gradually increasing texture; practicing responsive feeding, good hygiene, and proper food handling. 3 Furthermore, based on this study result, we find that mother CF knowledge (P = .002), child's age (P = .019), and household food security(P = .006) were the factors associated with appropriate CF practices in the context of COVID-19 outbreaks.…”
Section: Factors Related To Cf Practicesmentioning
confidence: 65%
“…A previous review from Indonesia indicated that nearly all children under 5 y of age consumed snacks daily ( 96 ). However, the consumption of energy-dense/nutrient‐poor snacks or SSBs during the CF period was not reported by other reviews ( 34 , 51 , 97 ). The consumption of SSBs and fast food has been associated with an increased risk of overweight/obesity among older children in Asia ( 49 , 82 ).…”
Section: Discussionmentioning
confidence: 88%
“…The special needs of some population groups, including infants, children, pregnant women, and the elderly, should be considered in planning responses to climate changes and healthy eating. In many countries, complementary diets given to infants after the age of six months are high volume and often low nutrient density, limiting nutrient intake (e.g., iron) (18). While nutrient density is important in infants and young children, a diet high in fiber becomes more important in adults for the prevention of chronic disease.…”
Section: Special Population Groupsmentioning
confidence: 99%
“…Reduction of both undernutrition and overconsumption (obesity) simultaneously implies a compression of the food consumption curve by balancing increased physical activity with energy intake. This approach requires improvements in food and nutrition equity within and between countries (18,109,145). Swinburn et al (132) describe an international pandemic of obesity, undernutrition, and climate change causing major health problems for humanity as a "syndemic."…”
Section: Implementing Change: What Will Be Needed?mentioning
confidence: 99%